Learning to Listen, Listening to Learn - Lantos, John D. (The Hastings Center report, 2016)
The dust-jacket photo of Eric Cassell portrays him as a magician. He wears a dark suit, a bow tie, and big dark-rimmed glasses. His head is tilted down; his forehead is massive; his eyes are intense. It is an interrogating look that is crucial to the central theme of his most recent books, The Nature of Healing: The Modern Practice of Healing and The Nature of Clinical Medicine: The Return of the Clinician.